Meta-Analysis Aerobic Exercise Improves Quality of Life in Breast Cancer Survivor - Citra Ayuningtiyas; Agus Kristiyanto; Bhisma Murti (Masters Program in Public Health, 2022)
Background: Cancer is one of the health problems throughout the world, the increasing mortality rate due to breast cancer is one of them because it is detected at an advanced stage. In 2018 breast cancer was at the top of the list impacting 2,088,849 (11.6%) world women every year and with an incidence of death of 626,679 (6.6%) cases. One category of intervention to improve the quality of life of breast cancer survivors that has developed in recent years is by means of aerobic exercise. This study aims to estimate the magnitude of the effect of aerobic exercise on the quality of life of breast cancer survivors.Subjects and Method: This study was a meta-analysis study with PICO as follows P = breast cancer survivors. I= aerobic exercise. C= no intervention. O= quality of life. The articles used in this study were obtained from several databases, namely PubMed, Science Direct, and Google Scholar. This article was collected for 2 months. The keywords to search for articles were as follows: “breast cancer” OR “ca mammae” OR “carcinoma mammae” OR “mammae cancer”AND aerobic OR “aerobic exercise” AND “quality of life” OR “QOL” AND “RCT” OR “randomized control trial” OR “cluster-randomized control trial”. The articles included in this study are full text articles with a Randomized Controlled Trial study design. Articles were analyzed using the Review Manager 5.3 application. The results of the meta-analysis are reported using the PRISMA flow diagram.Results: There are 9 articles that have been analyzed from California, America, Iran, Kosovo, Spain, England, Canada, Germany, and the Netherlands. Studies show that aerobic exercise intervention improves the quality of life of breast cancer survivors SMD= 0.14; 95% CI= -0.23 to 0.51), and the results were not statistically significant (p= 0.460).Conclusion: Aerobic exercise improves the quality of life of breast cancer survivors. Keywords: aerobic exercise, breast cancer survivors, quality of life Correspondence:Citra Ayuningtiyas. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: citratiyas2@gmail.com. Mobile: 085345903455.